Development of certified reference materials for four polyunsaturated fatty acid esters. (30th September 2022) - Chen, Weizhu; Jin, Wenhui; Zhang, Yiping; Fang, Hua; Chen, Hui; Zhuan, Hong; Huang, Xiaoyan
Highlights: Four purity CRMs of DHA-ME, DHA-EE, EPA-ME, and EPA-EE were developed. Certification of the four purity CRMs was performed by qNMR and mass balance approaches. Homogeneities and stabilities of the four purity CRMs were evaluated. Four purity CRMs have been approved as reference materials (GBW(E)091181), (GBW(E)091182), (GBW(E)091183), (GBW(E) 091211). Abstract: Certified reference materials (CRMs) with high accuracy and traceability are essential tools for the validation of analytical methods and calibration of equipment. In this study, purity CRMs for four polyunsaturated fatty acids (PUFAs) esters, namely, cis-(4, 7, 10, 13, 16, 19)- Docosahexaenoic acid methyl ester (DHA-ME), cis -4, 7, 10, 13, 16, 19- Docosahexaenoic acid ethyl ester (DHA-EE), cis-(5, 8, 11, 14, 17)- Eicosapentaenoic acid methyl ester (EPA-ME) and cis-(5, 8, 11, 14, 17)- Eicosapentaenoic acid ethyl ester (EPA-EE), were first developed according to the ISO Guide. The CRMs' purity values were assigned based on the average of quantitative nuclear magnetic resonance and mass balance approaches. The certified value with expanded uncertainties ( k  = 2, 95% confidence interval) were determined to be (98.8 ± 0.4) %, (99.0 ± 0.3) %, (98.9 ± 0.4) % and (98.9 ± 0.4) % for DHA-ME, DHA-EE, EPA-ME and EPA-EE, respectively. The four PUFAs esters were homogeneous and stable for 12 months at −4 °C and 7 days at 50 °C.